Single-ion conductor solid electrolyte, preparation method thereof and solid-state battery

By using single-ion conductor polymers and cyano-containing covalent organic frame fillers in lithium-ion batteries, the migration number and conductivity of alkali metal ions are improved, and the problems of lithium dendrites are solved and the polarization of concentration is improved. Safety and energy density of solid-state batteries.

CN119297386APending Publication Date: 2025-01-10THE HONG KONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411274398.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The dual-ion conductive polymer solid electrolytes in existing lithium-ion batteries have insufficient in lithium dendrites growth and concentration polarization, resulting in limited battery safety and energy density, and low room temperature ion conductivity, making it difficult to match the high-voltage positive electrode.

Method used

Using a single ion conductor polymer and a covalent organic frame filler containing cyano groups, anion is anchored through sulfonic acid alkali metal salt groups and sulfonimide alkali metal salt groups, and using cyano groups and alkali metal ions to form ions-couples Pole interaction improves the number of migration and conductivity of alkali metal ions.

Benefits of technology

Effectively inhibit concentration polarization and dendrite growth, improve lithium ion conductivity, improve high-voltage stability and energy density of solid-state batteries, and extend cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005039706180000021
    Figure BDA0005039706180000021
  • Figure BDA0005039706180000051
    Figure BDA0005039706180000051
  • Figure HDA0005039706190000011
    Figure HDA0005039706190000011
Patent Text Reader

Abstract

The invention relates to the field of batteries, and particularly discloses a single-ion conductor solid-state electrolyte, a preparation method thereof and a solid-state battery, the solid-state electrolyte comprises a single-ion conductor polymer and a cyano-group-containing covalent organic framework filler; the single ion conductor polymer contains sulfonic acid alkali metal salt groups and / or fluorine groups. According to the solid electrolyte, anions are anchored in a polymer framework of a single-ion conductor polymer to limit movement of the anions, only lithium ions are conducted in the solid electrolyte in the charging and discharging process, the transference number of the lithium ions is close to 1, and concentration polarization and dendritic crystal growth on the surface of a lithium negative electrode can be effectively inhibited. Besides, the cyano-containing covalent organic framework filler is rich in electron-withdrawing cyano groups, and the cyano-containing covalent organic framework filler can promote dissociation of lithium ions from a polymer skeleton through strong ion-dipole interaction with the lithium ions, so that the ionic conductivity is effectively improved, and the ionic conductivity reaches about 1mS cm <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a single ion conductor solid electrolyte and a preparation method thereof, and a solid-state battery. Background Art

[0002] Lithium-ion batteries have been widely used due to their high energy density and long cycle life. However, current commercial lithium-ion batteries use toxic and flammable liquid electrolytes, which can easily cause combustion and explosion once the battery experiences thermal runaway. In contrast, solid electrolytes have higher thermal stability, avoid the volatilization and leakage of liquid electrolytes, and help improve battery safety. In addition, the high mechanical strength of solid electrolytes can effectively inhibit the growth of lithium dendrites and prevent the battery from short-circuiting. The negative electrode can then match the high-capacity metallic lithium, significantly improving the energy density of secondary batteries.

[0003] Polymer electrolytes have good flexibility and can form good contact with electrodes. They are a type of solid electrolyte material with broad commercial prospects. However, lithium salts need to be added to polymer electrolytes to exhibit dual ion conductivity (lithium ions and anions). The lithium ion migration number is usually less than 0.5, resulting in severe concentration polarization and lithium dendrite growth. Single-ion conductor polymer electrolytes are a type of solid electrolyte with great potential, in which anions are anchored to the polymer skeleton. They can effectively inhibit concentration polarization and dendrite growth during battery cycling. However, in single-ion conductor electrolytes, it is difficult for lithium ions to dissociate from the polymer skeleton, resulting in low room temperature ionic conductivity; and the electrochemical window is narrow, the oxidation resistance is poor, and it is difficult to match the high-voltage positive electrode, which restricts its further development. Summary of the invention

[0004] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a solid electrolyte.

[0005] A second object of the present invention is to provide a method for preparing a solid electrolyte.

[0006] A third object of the present invention is to provide a solid-state battery.

[0007] A fourth object of the present invention is to provide application of the above-mentioned solid electrolyte and / or the above-mentioned preparation method in the field of batteries.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention provides a solid electrolyte comprising a single ion conductor polymer and a cyano-containing covalent organic framework filler; the single ion conductor polymer contains at least one of a sulfonic acid alkali metal salt group, a sulfonyl imide alkali metal salt group, and a fluorine group.

[0010] The polyanions (e.g., p-styrenesulfonate ions) in the solid electrolyte of the present invention are anchored in the polymer skeleton on the single-ion conductor polymer, and only alkali metal ions can migrate in the solid electrolyte, thereby obtaining single-ion conductive properties; the cyanide groups in the cyanide-containing covalent organic framework filler can promote the dissociation of alkali metal ions from the polyanion groups through ion-dipole interactions, thereby effectively improving the conductivity of alkali metal ions.

[0011] Preferably, the single ion conductor polymer contains a fluorine group and any group selected from a sulfonic acid alkali metal salt group and a sulfonimide alkali metal salt group; further preferably, the single ion conductor polymer contains a fluorine group and a sulfonic acid alkali metal salt group.

[0012] Preferably, the cyano-containing covalent organic framework filler is selected from COF316, 2DPPV-COF, sp 2 At least one of c-COF, COF-p-3Ph, COF-p-2Ph, and COF-m-3Ph.

[0013] Among them, the structural formula of COF316 is as follows:

[0014]

[0015] Preferably, the sulfonic acid alkali metal salt group is selected from a lithium sulfonate group, a sodium sulfonate group or a potassium sulfonate group. When the sulfonic acid alkali metal salt group is a lithium sulfonate group, the solid electrolyte at this time is suitable for lithium ion batteries; when the sulfonic acid alkali metal salt group is a sodium sulfonate group, the solid electrolyte at this time is suitable for sodium ion batteries; when the sulfonic acid alkali metal salt group is a potassium sulfonate group, the solid electrolyte at this time is suitable for potassium ion batteries.

[0016] Preferably, the sulfonyl imide alkali metal salt group is selected from a sulfonyl imide lithium group, a sulfonyl imide sodium group or a sulfonyl imide potassium group.

[0017] Preferably, the single ion conductor polymer is polymerized by polymerizing monomers; the polymerized monomers are selected from at least two of monomer A, monomer B, and monomer C; the monomer A is selected from at least one of alkali metal p-styrene sulfonate, alkali metal styrene trifluoromethanesulfonyl imide, and alkali metal methacrylate trifluoromethanesulfonyl imide; the monomer B is selected from at least one of hexafluorobutyl acrylate, 2-(perfluorobutyl)ethyl acrylate, and (2H-perfluoropropyl)-2-acrylate; the monomer C is selected from at least one of polyethylene glycol diacrylate and polyethylene glycol methyl ether methacrylate. Further preferably, the single ion conductor polymer is polymerized by alkali metal p-styrene sulfonate, hexafluorobutyl acrylate, and polyethylene glycol diacrylate.

[0018] Specifically, when the solid electrolyte is used in a lithium ion battery, the single ion conductor polymer is polymerized from at least one monomer selected from lithium p-styrene sulfonate, lithium 2-acrylamido-2-methylpropane sulfonate, and lithium 3-sulfopropyl acrylate, at least one monomer selected from hexafluorobutyl acrylate, 2-(perfluorobutyl)ethyl acrylate, and (2H-perfluoropropyl)-2-acrylate, and at least one monomer selected from polyethylene glycol diacrylate and polyethylene glycol methyl ether methacrylate.

[0019] When the solid electrolyte is used in a sodium ion battery, the single ion conductor polymer is polymerized from at least one monomer selected from sodium p-styrene sulfonate, sodium 2-acrylamido-2-methylpropane sulfonate, sodium 3-sulfopropyl acrylate, at least one monomer selected from hexafluorobutyl acrylate, 2-(perfluorobutyl)ethyl acrylate, (2H-perfluoropropyl)-2-acrylate, and at least one monomer selected from polyethylene glycol diacrylate and polyethylene glycol methyl ether methacrylate.

[0020] When the solid electrolyte is used in a potassium ion battery, the single ion conductor polymer is polymerized from at least one monomer selected from potassium p-styrene sulfonate, potassium 2-acrylamido-2-methylpropane sulfonate, potassium 3-sulfopropyl acrylate, at least one monomer selected from hexafluorobutyl acrylate, 2-(perfluorobutyl)ethyl acrylate, (2H-perfluoropropyl)-2-acrylate, and at least one monomer selected from polyethylene glycol diacrylate and polyethylene glycol methyl ether methacrylate.

[0021] Preferably, the solid electrolyte further contains a solvent.

[0022] Preferably, the solvent is selected from at least one of fluoroethylene carbonate and fluoropropylene carbonate.

[0023] Preferably, based on the total mass percentage of the solid electrolyte being 100%, the mass percentage of the cyano-containing covalent organic framework filler is 0.5% to 10%.

[0024] Preferably, the solid electrolyte is in a film shape; the film thickness of the solid electrolyte is 30 to 300 μm.

[0025] The second aspect of the present invention provides a method for preparing the solid electrolyte according to the first aspect of the present invention, comprising the following steps:

[0026] Mixing raw materials including a polymerizable monomer of a single ion conductor polymer, a cyano-containing covalent organic framework filler, and an optionally added solvent to obtain a precursor mixture;

[0027] The precursor mixture is subjected to a polymerization reaction to obtain the solid electrolyte.

[0028] Preferably, the preparation method comprises the following steps:

[0029] Mixing raw materials including the polymerization monomer of the single ion conductor polymer, the covalent organic framework filler containing a cyano group, and an optionally added solvent to obtain a precursor mixture;

[0030] The precursor mixture is mixed with a photoinitiator and polymerized into a film under light initiation to obtain the product.

[0031] Preferably, the added amount of the photoinitiator is 0.2% to 10% of the total mass of the precursor mixture.

[0032] Preferably, the photoinitiator is selected from at least one of 2-hydroxy-2-methylpropiophenone, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-(4-isopropylphenyl)-1-propanone and 2-hydroxy-2-methyl-1-(4-tert-butylphenyl)-1-propanone.

[0033] Preferably, the light initiation time is 3 to 60 minutes.

[0034] Preferably, the photoinitiation is initiated by ultraviolet light with a wavelength of 360 to 370 nm.

[0035] Preferably, the polymerizable monomer is selected from alkali metal p-styrenesulfonate, polyethylene glycol diacrylate and hexafluorobutyl acrylate.

[0036] Preferably, the mass ratio of the alkali metal salt of p-styrenesulfonate, polyethylene glycol diacrylate, and hexafluorobutyl acrylate is (1-8):(1-8):1.

[0037] Preferably, the mixing step employs ultrasonic mixing.

[0038] The third aspect of the present invention provides a solid-state battery, comprising the solid-state electrolyte described in the first aspect of the present invention, or the solid-state electrolyte prepared by the preparation method described in the second aspect of the present invention.

[0039] Preferably, the solid-state battery is a lithium-ion solid-state battery, a sodium-ion solid-state battery or a potassium-ion solid-state battery.

[0040] The fourth aspect of the present invention provides the application of the solid electrolyte described in the first aspect of the present invention and / or the preparation method described in the second aspect of the present invention in the field of batteries.

[0041] The beneficial effects of the present invention are as follows: compared with the conventional dual-ion conductive polymer solid electrolyte, the solid electrolyte of the present invention anchors the anions in the polymer skeleton of the single-ion conductive polymer to restrict their movement, and only the alkali metal ions are conducted in the solid electrolyte during the charge and discharge process, and the migration number of the alkali metal ions is close to 1, which can effectively inhibit concentration polarization and dendrite growth. In addition, the cyanide-containing covalent organic framework filler is rich in electron-withdrawing cyanide groups, which can promote the dissociation of alkali metal ions from the polymer skeleton through the strong ion-dipole interaction between the cyanide and the alkali metal ions, thereby effectively improving the ionic conductivity to 1 mS cm -1 The cyanide group can effectively inhibit the dissolution of transition metals in the positive electrode active material during the charging and discharging process, thereby effectively improving the high-voltage stability of the solid-state battery.

[0042] The solid-state battery in the present invention adopts a solid electrolyte containing a single-ion conductor polymer and a covalent organic framework filler containing a cyanide group. The cyanide group in the covalent organic framework filler inhibits the dissolution of metal ions by forming a strong coordination with the transition metal ions of the positive electrode active material, thereby effectively improving the high-voltage stability of the solid-state battery, and can effectively improve the energy density and cycle life of the battery, which is conducive to the development of the solid-state battery field. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The infrared absorption spectra of the single ion conductor solid electrolyte membranes of Example 1 and Comparative Example 1 are shown.

[0044] Figure 2 1 is a stress-strain curve diagram of the single ion conductor solid electrolyte membrane of Example 1 and Comparative Example 1.

[0045] Figure 3 The EIS AC impedance spectra of the single ion conductor solid electrolyte membranes of Example 1 and Comparative Example 1 are shown.

[0046] Figure 4 This is a test diagram of the lithium ion conductivity of the single ion conductor solid electrolyte membrane of Example 1 and Comparative Example 1.

[0047] Figure 5 1 is a chronoamperometric polarization curve diagram of the single ion conductor solid electrolyte membrane of Example 1 and Comparative Example 1.

[0048] Figure 6 Impedance spectra of the single ion conductor solid electrolyte membranes of Example 1 and Comparative Example 1 before and after polarization.

[0049] Figure 7 The linear voltammetric curves of the single ion conductor solid electrolyte membranes of Example 1 and Comparative Example 1 are shown.

[0050] Figure 8Graph showing the cycle performance of the NCM811|Li solid-state lithium metal battery assembled from the single ion conductor solid electrolyte membranes of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0051] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0052] In some embodiments of the present invention, the present invention provides a solid electrolyte comprising a single ion conductor polymer and a cyanide-containing covalent organic framework filler; the single ion conductor polymer contains at least one of a sulfonic acid alkali metal salt group, a sulfonyl imide alkali metal salt group, and a fluorine group.

[0053] In some embodiments of the present invention, the single ion conductor polymer contains a fluorine group and any group selected from a sulfonic acid alkali metal salt group and a sulfonimide alkali metal salt group; in some embodiments of the present invention, the single ion conductor polymer contains a fluorine group and a sulfonic acid alkali metal salt group.

[0054] In some embodiments of the present invention, the cyano-containing covalent organic framework filler is selected from COF316, 2DPPV-COF, sp 2 At least one of c-COF, COF-p-3Ph, COF-p-2Ph, and COF-m-3Ph.

[0055] The structural formula of COF316 is as follows:

[0056]

[0057] In some embodiments of the present invention, the sulfonate alkali metal salt group is selected from a lithium sulfonate group, a sodium sulfonate group or a potassium sulfonate group. When the sulfonate alkali metal salt group is a lithium sulfonate group, the solid electrolyte at this time is suitable for lithium ion batteries; when the sulfonate alkali metal salt group is a sodium sulfonate group, the solid electrolyte at this time is suitable for sodium ion batteries; when the sulfonate alkali metal salt group is a potassium sulfonate group, the solid electrolyte at this time is suitable for potassium ion batteries.

[0058] In some embodiments of the present invention, the single ion conductor polymer is polymerized by polymerizing monomers; the polymerized monomers are selected from at least two of monomers A, B, and C; monomer A is selected from at least one of alkali metal salts of p-styrene sulfonate, alkali metal salts of styrene trifluoromethanesulfonyl imide, and alkali metal salts of methacrylate trifluoromethanesulfonyl imide; monomer B is selected from at least one of hexafluorobutyl acrylate, 2-(perfluorobutyl)ethyl acrylate, and (2H-perfluoropropyl)-2-acrylate; monomer C is selected from at least one of polyethylene glycol diacrylate and polyethylene glycol methyl ether methacrylate. In some embodiments of the present invention, the single ion conductor polymer is polymerized by lithium p-styrene sulfonate, hexafluorobutyl acrylate, and polyethylene glycol diacrylate.

[0059] In some embodiments of the present invention, when the solid electrolyte is used in a lithium ion battery, the single ion conductor polymer is formed by polymerizing monomers selected from at least one of lithium p-styrene sulfonate, lithium 2-acrylamido-2-methylpropane sulfonate, and lithium 3-sulfopropyl acrylate, at least one of hexafluorobutyl acrylate, 2-(perfluorobutyl)ethyl acrylate, and (2H-perfluoropropyl)-2-acrylate, and at least one of polyethylene glycol diacrylate and polyethylene glycol methyl ether methacrylate.

[0060] In some embodiments of the present invention, when the solid electrolyte is used in a sodium ion battery, the single ion conductor polymer is formed by polymerizing monomers selected from at least one of sodium p-styrene sulfonate, sodium 2-acrylamido-2-methylpropane sulfonate, and sodium 3-sulfopropyl acrylate, at least one of hexafluorobutyl acrylate, 2-(perfluorobutyl)ethyl acrylate, and (2H-perfluoropropyl)-2-acrylate, and at least one of polyethylene glycol diacrylate and polyethylene glycol methyl ether methacrylate.

[0061] In some embodiments of the present invention, when the solid electrolyte is used in a potassium ion battery, the single ion conductor polymer is polymerized from at least one monomer selected from potassium p-styrene sulfonate, potassium 2-acrylamido-2-methylpropane sulfonate, potassium 3-sulfopropyl acrylate, hexafluorobutyl acrylate, 2-(perfluorobutyl)ethyl acrylate, at least one of (2H-perfluoropropyl)-2-acrylate, polyethylene glycol diacrylate, and at least one of polyethylene glycol methyl ether methacrylate.

[0062] In some embodiments of the present invention, the solid electrolyte further contains a solvent.

[0063] In some embodiments of the present invention, the solvent is selected from at least one of fluoroethylene carbonate and fluoropropylene carbonate.

[0064] In some embodiments of the present invention, taking the total mass percentage of the solid electrolyte as 100%, the mass percentage of the cyanide-containing covalent organic framework filler is 0.5% to 10%. For example, the mass percentage of the cyanide-containing covalent organic framework filler can be selected from 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, and 10%.

[0065] In some embodiments of the present invention, the solid electrolyte is in film form; the film thickness of the solid electrolyte is 30 to 300 μm, for example: the film thickness of the solid electrolyte can be selected from 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, and 300 μm.

[0066] In some embodiments of the present invention, the present invention provides a method for preparing a solid electrolyte, comprising the following steps:

[0067] Mixing a polymerizing monomer including a single ion conductor polymer, a cyano-containing covalent organic framework filler, and a solvent to obtain a precursor mixture;

[0068] The precursor mixture is subjected to a polymerization reaction to obtain a solid electrolyte.

[0069] In some embodiments of the present invention, the method for preparing the solid electrolyte in the present invention comprises the following steps:

[0070] Mixing raw materials including a polymerizable monomer of a single ion conductor polymer, a covalent organic framework filler containing a cyano group, and an optionally added solvent to obtain a precursor mixture;

[0071] The precursor mixture is mixed with a photoinitiator and then polymerized into a film under light initiation to obtain the product.

[0072] In some embodiments of the present invention, the amount of photoinitiator added is 0.2% to 10% of the total mass of the precursor mixture, for example: it can be selected from 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.4%, 3.8%, 4%, 4.4%, 4.5%, 4.8%, 5%, 5.4%, 5.8%, 6%, 6.4%, 6.6%, 7%, 7.5%, 8%, 8.4%, 9%, 9.4%, 9.8%, 10%.

[0073] In some embodiments of the present invention, the photoinitiator is selected from at least one of 2-hydroxy-2-methylpropiophenone, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-(4-isopropylphenyl)-1-propanone, and 2-hydroxy-2-methyl-1-(4-tert-butylphenyl)-1-propanone.

[0074] In some embodiments of the present invention, the light initiation time is 3 to 60 min; for example, the light initiation time can be selected from 3 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, and 60 min.

[0075] In some embodiments of the present invention, the photoinitiation is initiated by ultraviolet light with a wavelength of 360-370 nm.

[0076] In some embodiments of the present invention, the polymerizable monomer is selected from alkali metal p-styrenesulfonate, polyethylene glycol diacrylate and hexafluorobutyl acrylate.

[0077] In some embodiments of the present invention, the mass ratio of alkali metal p-styrenesulfonate, polyethylene glycol diacrylate, and hexafluorobutyl acrylate is (1-8):(1-8):1.

[0078] In some embodiments of the present invention, the mixing step employs ultrasonic mixing.

[0079] In some embodiments of the present invention, the present invention provides a solid-state battery, comprising the above-mentioned solid-state electrolyte, or the solid-state electrolyte prepared by the above-mentioned preparation method.

[0080] In some embodiments of the present invention, the solid-state battery is a lithium-ion solid-state battery, a sodium-ion solid-state battery, or a potassium-ion solid-state battery.

[0081] In some embodiments of the present invention, a solid-state battery includes a negative electrode shell, a spring, a gasket, a lithium sheet, a solid electrolyte membrane, a positive electrode sheet, and a positive electrode shell arranged in sequence.

[0082] In some embodiments of the present invention, the present invention provides application of the above-mentioned solid electrolyte and / or the above-mentioned preparation method in the field of batteries.

[0083] The implementation of the present invention is further described in detail below with reference to specific embodiments:

[0084] Example 1

[0085] This example provides a solid-state lithium metal battery, which is prepared by a preparation method comprising the following steps:

[0086] (1) Lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 were weighed in a mass ratio of 5:4:1:1:0.2 and dispersed in a DMSO solvent. 1 wt % of a photoinitiator, 2-hydroxy-2-methylpropiophenone (based on the total mass percentage of lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 being 100%), was added thereto, and then ultrasonicated for 2 h to obtain a precursor solution.

[0087] (2) The precursor solution was injected between two glass plates with a gap height of 160 μm, and the precursor solution was irradiated with 365 nm ultraviolet light for 30 minutes to solidify and generate a single ion conductor solid electrolyte membrane.

[0088] (3) The NCM811‖Li solid-state lithium metal battery in this example is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, single ion conductor solid electrolyte membrane, positive electrode sheet (NCM811), and positive electrode shell.

[0089] Example 2

[0090] This example provides a solid-state lithium metal battery, which is prepared by a preparation method comprising the following steps:

[0091] (1) Lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 were weighed in a mass ratio of 6:3:1:1:0.2 and dispersed in DMSO solvent, to which 0.5 wt % of photoinitiator 2-hydroxy-2-methylpropiophenone was added (based on the total mass percentage of lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 being 100%), followed by ultrasonication for 2 h to obtain a precursor solution.

[0092] (2) The precursor solution was injected between two glass plates with a gap height of 160 μm, and the precursor solution was irradiated with 365 nm ultraviolet light for 30 minutes to solidify and generate a single ion conductor solid electrolyte membrane.

[0093] (3) The NCM811‖Li solid-state lithium metal battery in this example is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, single ion conductor solid electrolyte membrane, positive electrode sheet (NCM811), and positive electrode shell.

[0094] Example 3

[0095] This example provides a solid-state lithium metal battery, which is prepared by a preparation method comprising the following steps:

[0096] (1) Lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 were weighed in a mass ratio of 7:2:1:1:0.2 and dispersed in DMSO solvent, to which 1 wt % of photoinitiator 2-hydroxy-2-methylpropiophenone was added (based on the total mass percentage of lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 being 100%), followed by ultrasonication for 2 h to obtain a precursor solution.

[0097] (2) The precursor solution was injected between two glass plates with a gap height of 160 μm, and the precursor solution was irradiated with 365 nm ultraviolet light for 30 minutes to solidify and generate a single ion conductor solid electrolyte membrane.

[0098] (3) The NCM811‖Li solid-state lithium metal battery in this example is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, single ion conductor solid electrolyte membrane, positive electrode sheet (NCM811), and positive electrode shell.

[0099] Example 4

[0100] This example provides a solid-state lithium metal battery, which is prepared by a preparation method comprising the following steps:

[0101] (1) Lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 were weighed in a mass ratio of 5:4:1:1:0.2 and dispersed in a DMSO solvent. 1 wt % of a photoinitiator, 2-hydroxy-2-methylpropiophenone (based on the total mass percentage of lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 being 100%), was added thereto, and then ultrasonicated for 2 h to obtain a precursor solution.

[0102] (2) The precursor solution was injected between two glass plates with a gap height of 100 μm, and the precursor solution was irradiated with 365 nm ultraviolet light for 30 minutes to solidify and generate a single ion conductor solid electrolyte membrane.

[0103] (3) The NCM811‖Li solid-state lithium metal battery in this example is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, single ion conductor solid electrolyte membrane, positive electrode sheet (NCM811), and positive electrode shell.

[0104] Example 5

[0105] This example provides a solid-state lithium metal battery, which is prepared by a preparation method comprising the following steps:

[0106] (1) Lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 were weighed in a mass ratio of 5:4:1:1:0.2 and dispersed in a DMSO solvent. 1 wt % of a photoinitiator, 2-hydroxy-2-methylpropiophenone (based on the total mass percentage of lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 being 100%), was added thereto, and then ultrasonicated for 2 h to obtain a precursor solution.

[0107] (2) The precursor solution was injected between two glass plates with a gap height of 160 μm, and the precursor solution was irradiated with 365 nm ultraviolet light for 5 minutes to solidify and generate a single ion conductor solid electrolyte membrane.

[0108] (3) The NCM811‖Li solid-state lithium metal battery in this example is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, single ion conductor solid electrolyte membrane, positive electrode sheet (NCM811), and positive electrode shell.

[0109] Example 6

[0110] This example provides a solid-state lithium metal battery, which is prepared by a preparation method comprising the following steps:

[0111] (1) Lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 were weighed in a mass ratio of 5:4:1:1:1 and dispersed in DMSO solvent. 1 wt % of photoinitiator 2-hydroxy-2-methylpropiophenone was added thereto (based on the total mass percentage of lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 being 100%), followed by ultrasonication for 2 h to obtain a precursor solution.

[0112] (2) The precursor solution was injected between two glass plates with a gap height of 160 μm, and the precursor solution was irradiated with 365 nm ultraviolet light for 30 minutes to solidify and generate a single ion conductor solid electrolyte membrane.

[0113] (3) The NCM811‖Li solid-state lithium metal battery in this example is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, single ion conductor solid electrolyte membrane, positive electrode sheet (NCM811), and positive electrode shell.

[0114] Example 7

[0115] This example provides a solid-state lithium metal battery, which is prepared by a preparation method comprising the following steps:

[0116] (1) Lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 were weighed in a mass ratio of 5:4:1:1:0.2 and dispersed in a DMSO solvent. 1 wt % of a photoinitiator, 2-hydroxy-2-methylpropiophenone (based on the total mass percentage of lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 being 100%), was added thereto, and then ultrasonicated for 2 h to obtain a precursor solution.

[0117] (2) The precursor solution was injected between two glass plates with a gap height of 300 μm, and the precursor solution was irradiated with 365 nm ultraviolet light for 10 minutes to solidify and generate a single ion conductor solid electrolyte membrane.

[0118] (3) The NCM811‖Li solid-state lithium metal battery in this example is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, single ion conductor solid electrolyte membrane, positive electrode sheet (NCM811), and positive electrode shell.

[0119] Example 8

[0120] This example provides a solid-state lithium metal battery, which is prepared by a preparation method comprising the following steps:

[0121] (1) Lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 were weighed in a mass ratio of 8:1:1:1:0.2 and dispersed in DMSO solvent. 1 wt % of photoinitiator 2-hydroxy-2-methylpropiophenone was added thereto (based on the total mass percentage of lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 being 100%), followed by ultrasonication for 2 h to obtain a precursor solution.

[0122] (2) The precursor solution was injected between two glass plates with a gap height of 300 μm, and the precursor solution was irradiated with 365 nm ultraviolet light for 10 minutes to solidify and generate a single ion conductor solid electrolyte membrane.

[0123] (3) The NCM811‖Li solid-state lithium metal battery in this example is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, single ion conductor solid electrolyte membrane, positive electrode sheet (NCM811), and positive electrode shell.

[0124] Example 9

[0125] This example provides a solid-state lithium metal battery, which is prepared by a preparation method comprising the following steps:

[0126] (1) Lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 were weighed in a mass ratio of 1:8:1:1:0.2 and dispersed in a DMSO solvent. 1 wt % of a photoinitiator, 2-hydroxy-2-methylpropiophenone (based on the total mass percentage of lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate, fluoroethylene carbonate and COF316 being 100%) was added thereto, followed by ultrasonication for 2 h to obtain a precursor solution.

[0127] (2) The precursor solution was injected between two glass plates with a gap height of 300 μm, and the precursor solution was irradiated with 365 nm ultraviolet light for 10 minutes to solidify and generate a single ion conductor solid electrolyte membrane.

[0128] (3) The NCM811‖Li solid-state lithium metal battery in this example is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, single ion conductor solid electrolyte membrane, positive electrode sheet (NCM811), and positive electrode shell.

[0129] Comparative Example 1

[0130] This example provides a solid-state lithium metal battery, which is prepared by a preparation method comprising the following steps:

[0131] (1) Lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate and fluoroethylene carbonate were weighed in a mass ratio of 5:4:1:1 and dispersed in a DMSO solvent. 1 wt % of a photoinitiator, 2-hydroxy-2-methylpropiophenone (based on the total mass percentage of lithium p-styrene sulfonate, polyethylene glycol diacrylate, hexafluorobutyl acrylate and fluoroethylene carbonate being 100%), was added thereto, and then ultrasonicated for 2 h to obtain a precursor solution.

[0132] (2) The precursor solution was injected between two glass plates with a gap height of 160 μm, and the precursor solution was irradiated with 365 nm ultraviolet light for 30 minutes to solidify and generate a single ion conductor solid electrolyte membrane.

[0133] (3) The NCM811‖Li solid-state lithium metal battery in this example is assembled in the order of negative electrode shell, spring sheet, gasket, lithium sheet, single ion conductor solid electrolyte membrane, positive electrode sheet (NCM811), and positive electrode shell.

[0134] Performance Test:

[0135] The infrared absorption spectra of the single ion conductor solid electrolyte membranes prepared in Example 1 and Comparative Example 1 were tested respectively. Figure 1 As shown. Figure 1 It can be seen that both curves have obvious peaks of lithium sulfonate groups (SO3Li), and the characteristic peak of cyanide can be observed on the curve of Example 1. Compared with Comparative Example 1, the peaks belonging to the lithium sulfonate groups are significantly red-shifted when COF316 filler is added to the single ion conductor solid electrolyte membrane of Example 1, indicating that the cyanide groups on the COF316 skeleton have obvious cation-dipole interactions with the lithium sulfonate groups.

[0136] The stress-strain curves of the single ion conductor solid electrolyte membranes prepared in Example 1 and Comparative Example 1 were tested respectively. Figure 2 As shown. Figure 2 It can be seen that after adding COF316 filler, the maximum tensile strength of the single-ion conductor solid electrolyte of Example 1 increases to 1.48 MPa, which is 6.2 times (0.24 MPa) of the pure single-ion conductor polymer in Example 1, further indicating that the introduction of COF316 filler can significantly improve the mechanical properties of the single-ion conductor solid electrolyte membrane.

[0137] The EIS AC impedance spectra of the single ion conductor solid electrolyte membranes prepared in Example 1 and Comparative Example 1 were tested respectively. Figure 3 As shown, the lithium ion conductivity of the single ion conductor solid electrolyte membrane prepared in the corresponding embodiment 1 and comparative example 1 is as follows Figure 4 As shown. Figure 3 and Figure 4 It can be seen that the lithium ion conductivity of the single ion conductor solid electrolyte membrane with COF316 filler added in Example 1 at room temperature is 0.92 mS cm -1 , which is significantly higher than the lithium ion conductivity of the pure polymer single ion conductor solid electrolyte without COF316 filler in Comparative Example 1 (0.2 mS cm -1 ); further indicates that after the COF316 filler is introduced into the present invention, the cyano group on its skeleton can promote the dissociation of lithium ions from the polymer skeleton through the strong ion-dipole interaction between the lithium ions, thereby effectively improving the ionic conductivity.

[0138] The chronoamperometric polarization curves and impedance spectra before and after polarization of the single ion conductor solid electrolyte membranes prepared in Example 1 and Comparative Example 1 were tested respectively. The specific test results are as follows: Figure 5 and Figure 6 As shown, Figure 5 (a) and Figure 5 (b) are chronoamperometric polarization curves of the single ion conductor solid electrolyte membranes prepared in Example 1 and Comparative Example 1, Figure 6 (a) and Figure 6 (b) are impedance spectra of the single ion conductor solid electrolyte membranes prepared in Example 1 and Comparative Example 1 before and after polarization. Figure 5 and Figure 6 It can be seen that the lithium ion migration number of the single ion conductor solid electrolyte membrane with COF316 filler added in Example 1 at room temperature is as high as 0.94, which is better than the lithium ion migration number (0.78) of the pure polymer single ion conductor solid electrolyte membrane without COF316 filler in Comparative Example 1, further indicating that the single ion conductor solid electrolyte membrane of the present invention anchors the anions to the polymer skeleton to restrict their movement, so that Example 1 has a high lithium ion migration number, thereby effectively inhibiting concentration polarization and dendrite growth on the surface of the lithium negative electrode. In addition, the negatively charged cyanide group on the COF316 skeleton can limit the migration of free sulfonate ions in the electrolyte through electrostatic repulsion, further improving the lithium ion migration number.

[0139] The linear voltammetric curves (LSV) of the single ion conductor solid electrolyte membranes prepared in Example 1 and Comparative Example 1 were tested respectively. The specific test results are as follows: Figure 7 As shown. Figure 7 It can be seen that the oxidation potential (5.1V) of the single ion conductor solid electrolyte with COF316 filler added in Example 1 is significantly higher than that of the pure polymer single ion conductor solid electrolyte (4.6V) in the comparative example, indicating that the cyano group on the COF316 filler skeleton of the present invention can form a protective layer on the positive electrode surface, avoiding the side reaction between the positive electrode active material and the electrolyte, thereby widening the electrochemical stability window.

[0140] The cycle performance of the NCM811||Li solid-state lithium metal battery assembled by the single ion conductor solid electrolyte membrane in Example 1 and Comparative Example 1 was tested respectively. The specific test results are as follows: Figure 8 As shown. Figure 8 It can be seen that the pure polymer single ion conductor solid electrolyte in Comparative Example 1 decays to 93.0 mAh g after only 80 cycles at a current density of 0.5 C. -1 The capacity retention rate is 49.2%. In contrast, the battery based on the single ion conductor solid electrolyte in Example 1 still maintains a discharge capacity of 150.9 mAh g after 193 cycles at a current density of 0.5 C. -1, the capacity retention rate is 81.9%, indicating that the solid electrolyte in the present invention has a battery cycle performance that matches the high-voltage positive electrode NCM811. By comparing Example 1 with Comparative Example 1, it can be seen that the present invention introduces COF316 filler, and the rich cyano groups on its skeleton can effectively inhibit the dissolution of transition metals in NCM811, thereby effectively improving the high-voltage cycle stability of solid-state batteries.

[0141] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A solid electrolyte, characterized in that: The invention comprises a single ion conductor polymer and a covalent organic framework filler containing a cyano group; the single ion conductor polymer contains at least one of a sulfonic acid alkali metal salt group, a sulfonyl imide alkali metal salt group and a fluorine group.

2. The solid electrolyte according to claim 1, characterized in that: The cyano-containing covalent organic framework filler is selected from COF316, 2DPPV-COF, sp 2 At least one of c-COF, COF-p-3Ph, COF-p-2Ph, and COF-m-3Ph; and / or, the alkali metal sulfonate group is selected from a lithium sulfonate group, a sodium sulfonate group or a potassium sulfonate group; and / or, the sulfonyl imide alkali metal salt group is selected from a sulfonyl imide lithium group, a sulfonyl imide sodium group or a sulfonyl imide potassium group; And / or, the single ion conductor polymer is polymerized by polymerizing monomers; the polymerizing monomers are selected from at least two of monomer A, monomer B, and monomer C; the monomer A is selected from at least one of alkali metal salts of p-styrene sulfonate, alkali metal salts of styrene trifluoromethanesulfonyl imide, and alkali metal salts of methacrylate trifluoromethanesulfonyl imide; the monomer B is selected from at least one of hexafluorobutyl acrylate, 2-(perfluorobutyl)ethyl acrylate, and (2H-perfluoropropyl)-2-acrylate; The monomer C is selected from at least one of polyethylene glycol diacrylate and polyethylene glycol methyl ether methacrylate.

3. The solid electrolyte according to claim 1, characterized in that: The solid electrolyte further contains a solvent.

4. The solid electrolyte according to claim 1, characterized in that: Taking the total mass percentage of the solid electrolyte as 100%, the mass percentage of the cyanide-containing covalent organic framework filler is 0.5% to 10%.

5. The solid electrolyte according to any one of claims 1 to 4, characterized in that: The solid electrolyte is in a film shape; the film thickness of the solid electrolyte is 30 to 300 μm.

6. The method for preparing a solid electrolyte according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing raw materials including a polymerizable monomer of a single ion conductor polymer, a covalent organic framework filler containing a cyano group, and an optionally added solvent to obtain a precursor mixture; The precursor mixture is subjected to a polymerization reaction to obtain the solid electrolyte.

7. The method for preparing a solid electrolyte according to claim 6, characterized in that: The step of the polymerization reaction is: mixing the precursor mixture with a photoinitiator and polymerizing the mixture under light initiation to form a film to obtain the solid electrolyte.

8. The method for preparing a solid electrolyte according to claim 7, characterized in that: The amount of the photoinitiator added is 0.2% to 10% of the total mass of the precursor mixture; And / or, the photoinitiator is selected from at least one of 2-hydroxy-2-methylpropiophenone, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-(4-isopropylphenyl)-1-propanone, and 2-hydroxy-2-methyl-1-(4-tert-butylphenyl)-1-propanone; And / or, the light initiation time is 3 to 60 minutes; And / or, the photoinitiation is initiated by ultraviolet light with a wavelength of 360 to 370 nm; And / or, the polymerizable monomer is selected from alkali metal p-styrene sulfonate, polyethylene glycol diacrylate and hexafluorobutyl acrylate; the mass ratio of alkali metal p-styrene sulfonate, polyethylene glycol diacrylate and hexafluorobutyl acrylate is (1-8): (1~8):1; And / or, the mixing step adopts ultrasonic mixing.

9. A solid-state battery, characterized in that: The invention comprises the solid electrolyte according to any one of claims 1 to 5, or the solid electrolyte prepared by the preparation method according to any one of claims 6 to 8.

10. Use of the solid electrolyte according to any one of claims 1 to 5 and / or the preparation method according to any one of claims 6 to 8 in the field of batteries.